Modelling and analysis of performance for biogas fuelled gas engine using MATLAB / Indran Kunusilin - Indran , Kunusilin (2021)
A wide-ranging performance evaluation of a multi-cylinder gas engine operating wit biogas as a fuel were studied based on its performance parameters such as effective power, torque, SFC, MEP and Thermal Efficiency and its HRR analysis with the aid of modeling software, MATLAB. The analysis and performance study were used based on the thermodynamic model of an Otto cycle, which is based on the gas engines used. Parameters such as cylinder pressure with domain of crank angle and heat addition model (using Wiebe function ) were studied to model the and analyze the HRR .Besides that , the contributing factors in the efficiency and performance of the engine were deduced such as fluctuating HRR and increased thermal efficiency determining the performance optimization of the engine . The results obtain from the study were compared using the trend demonstrated with similar gas engine models. This research would set a milestone to extended research on the gas engines used in the industrial scale for performance enhancement and optimization.